PERUBAHAN POLA PERILAKU SOSIAL-EKONOMI MASYARAKAT SUB-URBAN DENGAN MENGELOLA HOME INDUSTRY KERIPIK TEMPE DI KABUPATEN PONOROGO - Sudarmiani Sudarmiani; MTh. Kuswariningsih (IKIP PGRI MADIUN, 2016)
This study aims to describe and analyze the behavior patterns of socio-economic sub-urban to manage home industry in increasing family income. The data collection technique used in the research are: (1) observations of doing a shoot (camera/visual), (2) a structured interview, (3) depth interview, and (3) create a life history. The results showed that agricultural sector move to other sectors for various reasons. This condition opens non-agricultural activities for the sub-urban community. One of the non-farm activities is the developing of home industry of Tempe chips. This business is a kind of home industry with a low profit. It requires relatively little capital, comes from savings, family loans or borrow from gathering. The family management system is used in this home industry. This is as the effect of uncertain condition of capital and marketing patterns. This home industry can not achieve an affordable paying system.